(untitled) (Research, Society and Development, 2023)
Introduction: Cancer is a general term that encompasses more than 100 categories of diseases that have in common the disordered growth of cells, causing functional disorders, cancer being one of these disorders. In view of this, there is cervical cancer caused by the Human Papilloma Virus, which results in the third neoplasm that most affects women. Therefore, studies on the subject are relevant for qualified assistance in preventing this disease. Objective: To identify in the literature how nurses can act in the prevention of cervical cancer. Methodology: This is an integrative literature review carried out in the Virtual Health Library (VHL), with the following inclusion criteria: articles published between 2016 and 2023, in Portuguese, English and Spanish, complete and freely available, used Bardin’s Content Analysis. Results: It was found in the fifteen articles analyzed that the role of nurses in preventing cervical cancer are behavioral, social and cognitive interventions through health education. Conclusion: Nurses have an extremely important role in preventing this neoplasm.